2004
DOI: 10.2139/ssrn.556348
|View full text |Cite
|
Sign up to set email alerts
|

Equilibrium with a Market of Permits

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Greysen et al [7] successfully applied neural networks to stock index forecasting. Jouvet et al [8] demonstrated that the prediction performance of neural networks for time series forecasting problems was comparable to that of ARMA models through comparative tests. Daams and Sijtsma [9]compared statistical models such as ARMA, exponential smoothing, and portfolio forecasting with neural network models, and the comparison showed that neural network forecasts outperformed traditional methods in statistics, especially for multi-step forecasting, where the advantages of neural networks were more obvious.…”
Section: Current State Of Economic Forecasting Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Greysen et al [7] successfully applied neural networks to stock index forecasting. Jouvet et al [8] demonstrated that the prediction performance of neural networks for time series forecasting problems was comparable to that of ARMA models through comparative tests. Daams and Sijtsma [9]compared statistical models such as ARMA, exponential smoothing, and portfolio forecasting with neural network models, and the comparison showed that neural network forecasts outperformed traditional methods in statistics, especially for multi-step forecasting, where the advantages of neural networks were more obvious.…”
Section: Current State Of Economic Forecasting Researchmentioning
confidence: 99%
“…Steps (1) to ( 5) are identical to the conventional GM(1,1) model modeling and will not be repeated here. (8) Let us calculate the model parameters c and A as follows:…”
Section: Improving Ba-lstm Models By Combining Grey Modelsmentioning
confidence: 99%
“…Production function (1) is consistent with the common modeling method where the flow of pollution is a by‐product of the final output. After some mathematical manipulation of the Stokey (1998) model, the flow of pollution can equivalently be treated as a necessary input in the production function (Brock & Taylor, 2005; Jouvet et al, 2005a; Ono, 2002; Prieur et al, 2013). This is a convenient modeling framework for comparing pollution permits and green taxes.…”
Section: The Modelmentioning
confidence: 99%
“…This framework not only captures the effect of production activities on the environment but also is in line with the usual modeling approach that pollution is a by‐product of and is proportional to production. Another strand of the literature mathematically transforms the setup in Stokey (1998) and equivalently treats pollution as a necessary input in production, thus facilitating the analysis and comparison of pollution permits (Jouvet et al, 2005a; Ono, 2002; Prieur et al, 2013) and green taxes (Chen et al, 2015) within a dynamic general equilibrium framework.…”
Section: Introductionmentioning
confidence: 99%
“…If q t = 0, the economy without an environmental tax experiences unbounded levels of wages, interest rates, and pollution in every period; in other words, the economy without an environmental tax is not well defined if q t = 0 (see Jouvet, Michel, and Rotillon, 2005b, for a discussion of this point). Therefore, the assumption of q t > 0 simulates a realistic situation in which the level of pollution is high but remains limited in an economy without environmental taxation.…”
Section: Firmsmentioning
confidence: 99%